2004
DOI: 10.1136/bmj.37945.566632.ee
|View full text |Cite
|
Sign up to set email alerts
|

Delivering interventions for depression by using the internet: randomised controlled trial

Abstract: Objective To evaluate the efficacy of two internet interventions for community-dwelling individuals with symptoms of depression-a psychoeducation website offering information about depression and an interactive website offering cognitive behaviour therapy. Design Randomised controlled trial. Setting Internet users in the community, in Canberra, Australia. Participants 525 individuals with increased depressive symptoms recruited by survey and randomly allocated to a website offering information about depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
673
6
17

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 775 publications
(743 citation statements)
references
References 20 publications
31
673
6
17
Order By: Relevance
“…For internet-based treatment without therapist support for symptoms of depression, we found effect sizes (compared to inactive control groups) from 0 to 0 . 4 (Clarke et al 2002(Clarke et al , 2005Patten, 2003;Christensen et al 2004). The effect size for the control condition in our study roughly corresponds with effect sizes found in other studies on internet-based treatment for symptoms of depression : we found effect sizes ranging from 0 .…”
Section: Discussionsupporting
confidence: 76%
“…For internet-based treatment without therapist support for symptoms of depression, we found effect sizes (compared to inactive control groups) from 0 to 0 . 4 (Clarke et al 2002(Clarke et al , 2005Patten, 2003;Christensen et al 2004). The effect size for the control condition in our study roughly corresponds with effect sizes found in other studies on internet-based treatment for symptoms of depression : we found effect sizes ranging from 0 .…”
Section: Discussionsupporting
confidence: 76%
“…Although we could not find any CCBT interventions utilizing NLG, positive results from their application in related areas (Barak et al 2008) make them a prime candidate for future research. For example, the efficacy of Moodgym (Christensen, Griffiths and Jorm 2004), one of the pioneering tools for online CBT, showed that it was effective in reducing depression and dysfunctional thinking and in increasing understanding about CBT techniques. Since then many other CBT-based interventions have been developed and evaluated for the treatment of different mental health problems (Barak and Grohol 2011).…”
Section: Interactive Self-guided Interventionsmentioning
confidence: 99%
“…Materials for guided self-management are increasingly available, both in the form of booklets and toolkits 28,29 and online interactive programs. 30 The NICE guidelines identify psychological treatment specifically focused on depression, such as problem solving therapy and brief CBT, as treatment options for mild and moderate depression. 31 According to Bilsker et al, 32 nearly 10% of the population visit a physician for depression in a given year, yet most receive less than 3 visits.…”
Section: Implications For Treatmentmentioning
confidence: 99%